Close follow‐up is associated with fewer stricture formation and results in earlier detection of histological relapse in the long‐term management of eosinophilic esophagitis. Issue 3 (5th April 2022) - Bon, Lorenz; Safroneeva, Ekaterina; Bussmann, Christian; Biedermann, Luc; Schreiner, Philipp; Vavricka, Stephan R.; Schoepfer, Alain M.; McCright‐Gill, Talaya; Simon, Hans‐Uwe; Straumann, Alex; Chehade, Mirna; Greuter, Thomas
Abstract: Background and aims: No recommendations exist regarding optimal follow‐up schedule in patients with eosinophilic esophagitis (EoE) under maintenance treatment. Methods: We retrospectively evaluated a long‐term surveillance concept at the Swiss EoE clinic, where clinical, endoscopic and histological disease activity is assessed annually regardless of EoE symptoms. Data on 159 adult patients under maintenance steroid treatment with available follow‐up were analyzed. Patients were classified as having close (duration between visits <18 months) or non‐close follow‐up (≥18 months). Results: We analyzed a total of 309 follow‐up visits of 159 patients (123 males, age at diagnosis 38.9 ± 15.4 years). 157 (51%) visits were within a close follow‐up schedule (median duration between visits of 1.0 years (interquartile range (IQR) 0.9–1.2)), while 152 visits (49%) were not (median duration between visits 2.9 years (IQR 2.0–4.1)). There was no difference regarding ongoing clinical, endoscopic, and histological disease activity, and adherence to prescribed steroid treatment between the two groups. However, stricture formation was significantly less frequently observed at visits within a close follow‐up schedule (22.9 vs. 33.6%, p  = 0.038). Absence of close follow‐up was a significant risk factor for stricture development in a multivariate regression model. Patients who achieved histological remission and were followed within a close‐follow‐up schedule had significantly earlier detection of histological relapse compared to patients not within such close follow‐up. Conclusion: Close follow‐up is associated with fewer stricture formation and appears to result in earlier detection of histological relapse in patients with eosinophilic esophagitis. We advocate for regular assessment of disease activity (every 12–18 months) in order to detect relapsing disease as early as possible, and therefore potentially minimize the risk for EoE complications.